Microengineered human amniotic ectoderm tissue array for high-content developmental phenotyping. (September 2019) - Nasr Esfahani, Sajedeh; Shao, Yue; Resto Irizarry, Agnes M.; Li, Zida; Xue, Xufeng; Gumucio, Deborah L.; Fu, Jianping
Abstract: During early post-implantation human embryogenesis, the epiblast (EPI) within the blastocyst polarizes to generate a cyst with a central lumen. Cells at the uterine pole of the EPI cyst then undergo differentiation to form the amniotic ectoderm (AM), a tissue essential for further embryonic development. While the causes of early pregnancy failure are complex, improper lumenogenesis or amniogenesis of the EPI represent possible contributing factors. Here we report a novel AM microtissue array platform that allows quantitative phenotyping of lumenogenesis and amniogenesis of the EPI and demonstrate its potential application for embryonic toxicity profiling. Specifically, a human pluripotent stem cell (hPSC)-based amniogenic differentiation protocol was developed using a two-step micropatterning technique to generate a regular AM microtissue array with defined tissue sizes. A computer-assisted analysis pipeline was developed to automatically process imaging data and quantify morphological and biological features of AM microtissues. Analysis of the effects of cell density, cyst size and culture conditions revealed a clear connection between cyst size and amniogenesis of hPSC. Using this platform, we demonstrated that pharmacological inhibition of ROCK signaling, an essential mechanotransductive pathway, suppressed lumenogenesis but did not perturb amniogenic differentiation of hPSC, suggesting uncoupled regulatory mechanisms for AM morphogenesis vs. cytodifferentiation. The AM microtissue array was further applied to screen a panel of clinically relevant drugs, which successfully detected their differential teratogenecity. This work provides a technological platform for toxicological screening of clinically relevant drugs for their effects on lumenogenesis and amniogenesis during early human peri-implantation development, processes that have been previously inaccessible to study.